Conscience and authority in the Medieval church - Murray, Alexander 1934- (Oxford Univ. Press, 2015)
Confession before 1215 -- Confession as a historical source in the thirteenth century -- Counselling in medieval confession -- Archbishop and mendicants in thirteenth-century Pisa -- Excommunication and conscience in the Middle Ages